Transesophageal Versus Surface Electromyography of the Diaphragm in Ventilated Subjects - Lokin, Joost Lc; Dulger, Soray; Glas, Gerie J; Horn, Janneke (Respiratory care, 2020)
Detection of diaphragmatic muscle activity during invasive ventilation may provide valuable information about patient-ventilator interactions. Transesophageal electromyography of the diaphragm ([Formula: see text]) is used in neurally adjusted ventilatory assist. This technique is invasive and can only be applied with one specific ventilator. Surface electromyography of the diaphragm ([Formula: see text]) is noninvasive and can potentially be applied with all types of ventilators. The primary objective of our study was to compare the ability of diaphragm activity detection between [Formula: see text] and [Formula: see text]. In this single-center pilot study, [Formula: see text] and [Formula: see text] recordings were obtained simultaneously for 15 min in adult subjects in the ICU who were invasively ventilated. The number of breathing efforts detected by [Formula: see text] and [Formula: see text] were determined. The percentage of detected breathing efforts by [Formula: see text] compared with [Formula: see text] was calculated. Temporal and signal strength relations on optimum recordings of 10 breaths per subject were also compared. The Spearman correlation coefficient was used to determine the correlation between [Formula: see text] and [Formula: see text]. Agreement was calculated by using Bland-Altman statistics. Fifteen subjects were included. The [Formula: see text] detected 3,675 breathing efforts, of which 3,162 (86.0%) were also detected by [Formula: see text]. A statistically significant temporal correlation (r = 0.95, < .001) was found between [Formula: see text] and [Formula: see text] in stable recordings. The mean difference in the time intervals between both techniques was 10.1 ms, with limits of agreement from -410 to 430 ms. Analysis of our results showed that [Formula: see text] was not reliable for breathing effort detection in subjects who were invasively ventilated compared with [Formula: see text]. In stable recordings, however, [Formula: see text] and [Formula: see text] had excellent temporal correlation and good agreement. With optimization of signal stability, [Formula: see text] may become a useful monitoring tool.